Invaders of Langat River: introduction of varied vermiculated sailfin catfish, Pterygoplichthys disjunctivus - Anand Prakash, S. P.; Mohamed, N. A.; Azmai, M. N. A.; Abu Bakar, A.; Othman, R.; Abdul Ghani, F. (Institute of Physics Publishing, 2022)
Globally and locally, invasive aquatic species pose a major threat towards aquatic ecosystems. Among the most successful of these aquatic invaders in Malaysian freshwater river systems is the vermiculated sailfin catfish or Pterygoplichthys disjunctivus. The study is conducted in Langat River, a subsidiary of the Selangor River basin which flows through the capital and high population density areas of the country. The impact of the species can be seen through its overpopulation and high density in the river due to the absence of natural predators and extremely high fecundity. This study provides the first report on the occurrence of introduced vermiculated sailfin catfish, P. disjunctivus, from Langat River, where the P. pardalis had been previously reported. In this study, random sampling exercises were conducted by using gill nets in a stretch of the Langat River. Out of 24 samples of Pterygoplichthys obtained, 11 were of P. pardalis. This was further confirmed by the morphometric and meristic characters as well as the patterns on the fish. Furthermore, during the sampling, we also described a new body pattern Pterygoplichthys, which does not fit both P. pardalis and P. disjunctivus entirely. The new body pattern of Pterygoplichthys, could be the result of hybridization between both species or variation patterns within the same species. However, a deeper study is necessary to be conducted to confirm this claim.